2006
DOI: 10.1177/1744987106068497
|View full text |Cite
|
Sign up to set email alerts
|

Seconding healthcare assistants to a pre-registration nursing course

Abstract: Attrition from traditional pre-registration nursing programmes in the United Kingdom continues to be substantial and, once qualified, new staff nurses experience a number of challenges in adapting to their new role. A possible solution, strongly favoured by the current government, is to second existing healthcare assistants onto pre-registration programmes. The premise is that, because of their previous caring experience and exposure to work in the National Health Service, secondees will be more committed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Those making the transition report feeling unprepared for the role (Thomas et al 2012) likening it to being thrown in at the deep end (Feng andTsai 2012, Duchscher 2009). Increased responsibility and accountability (Banks et al 2011, Higgins et al 2010, fear of failure (Gould et al 2006), a perceived lack of clinical skills ), feelings of vulnerability and inadequacy (Banks et al 2011) together with the unrealistic expectations of other staff have been reported as the greatest sources of stress.…”
Section: Introductionmentioning
confidence: 99%
“…Those making the transition report feeling unprepared for the role (Thomas et al 2012) likening it to being thrown in at the deep end (Feng andTsai 2012, Duchscher 2009). Increased responsibility and accountability (Banks et al 2011, Higgins et al 2010, fear of failure (Gould et al 2006), a perceived lack of clinical skills ), feelings of vulnerability and inadequacy (Banks et al 2011) together with the unrealistic expectations of other staff have been reported as the greatest sources of stress.…”
Section: Introductionmentioning
confidence: 99%
“…The need for the development of the unqualified worker role within the NHS generally is discussed and proposed by the RCN (2009) and as well in papers by Fowler (2003), Gould et al (2006) and Castledine (2004). These latter three authors also argue strongly for a programme of CPD and training for nursing aides since the nursing profession over the years has been dependent on them to complete the workforce quota and carry out essential patient care.…”
Section: Background Literaturementioning
confidence: 99%
“…Once at the top of band 5, options are limited to remain on this band and receiving the standard yearly incremental pay rises if applicable OR they can look to enter nurse training given available funding and support. This may certainly suit many HCAs or Nursery Nurses but Gould et al (2006) acknowledges that this option is not for everyone. In their qualitative research examining the role transition of newly qualified staff nurses who had previously been employed as health care assistants and then seconded to a preregistration nursing course, uptake was low.…”
Section: Background Literaturementioning
confidence: 99%
“…Answering questions All recruitment activities involving student ambassadors include time spent alone with prospective students to give honest and candid answers to questions. Gould et al (2004), in an evaluation of a scheme to second healthcare assistants (HCAs) to pre-registration nursing, reported that, despite HCAs being challenged by the theoretical aspects of the course, especially science, overall they were satisfied with the course and performed well. Placements, as well as the competing demands of home, family and academic study, are always a source of interest for would-be applicants.…”
Section: Activities and Actionsmentioning
confidence: 99%
“…Lindop (1991) suggested that stress associated with practice and placements is often a reason for leaving nursing. Gould et al (2004) concluded that secondments represented value for money because wastage rates were low and a high proportion of staff readily returned to work in these areas. The student ambassadors try to create a realistic picture -without being too negative -and, at the same time, share their own coping strategies.…”
Section: Activities and Actionsmentioning
confidence: 99%